Balloon valvuloplasty in two dogs with aortic valve stenosis showing congestive heart failure - Tomohiko Yoshida; Kastuhiro Matsuura; Seijirow Goya; Danfu Ma; Kazumi Shimada; Pitipat Kitpipatkun; Aki Takeuchi; Akiko Uemura; Ryou Tanaka (Veterinární Medicína, 2020)
A 10-year-old female Papillon and a 1-year-old male Golden Retriever were presented to the Tokyo University of Agriculture and Technology for a second opinion on an aortic valve stenosis (AS). The aortic flow rate was not as high as it should have been (the aortic flow velocity for case 1 and case 2 was 2.82 m/s and 3.96 m/s, respectively). However, the AS was suspected to be an exacerbating factor in the congestive heart failure, so that a balloon valvuloplasty was conducted. As a result, the congestion and clinical symptoms were much improved in both cases. In conclusion, in cases with an AS, in which afterload is a key factor for the exacerbation of the congestion, a balloon aortic valvuloplasty may reduce the afterload and consequently lead to an improvement in the congestion.